Pengaruh Budaya Jepang Terhadap Pola Perilaku Mahasiswa Indonesia Di MANABI Gaigogakuin - Tya Gita Gauri, Ni Putu; Wayan Nurita; Wayan Meidariani (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
This thesis discusses the influence of Japanese culture on the behavior patterns of Indonesian students at MANABIGaigogakuin. The Japanese culture that affect Indonesian students at MANABI Gaigogakuin such as pop culture, part-time work, punctual culture and nomikai. This thesis uses the theory of hegemony proposed by Antonio Gramsci and uses two other supporting theories related to the existing problems. Sources of data in this study using primary data sources. The data were obtained using the proficient method with questionnaires and interviews with 8 Indonesian student respondents who had studied at MANABI Gaigogakuin. The results of this study are that each of the influences of Japanese culture such as pop culture, part-time work, punctual culture and nomikai has a driving factor. The driving factor of the influence of Japanese culture such as pop culture is the need for love of things you like such as anime like Naruto, Kimetsu no Yaiba and others. The driving factor for part-time work culture is the physiological needs to fulfill living expenses in Japan so as to form an independent personality. The driving factor of the punctual culture is the need for security and recognition from others that you can adapt to the Japanese environment and also get good grades in school. And the driving factor for nomikai culture is wanting to establish social relations with Japanese people, including co-workers. The four cultures that influence the behavior of foreign students at MANABI Gaigogakuin have positive and negative impacts, such as pop culture which has a positive impact, namely students can more freely express themselves through their preferred dress style, while the negative impact is being consumptive because they collect a lot of objects.